Epidemiology and Classification of Mastitis - Cobirka, Maros; Tancin, Vladimir; Slama, Petr (Animals, 2020)
Farmers should focus on milk quality over quantity because milk that contains unsuitable components and/or antibiotic residues, or has a high somatic cell count, cannot be used in food production and thereby results in reduced milk yield. One of the main problems affecting the ultimate milk yield of dairy cows is mastitis. This disease is the most serious economic and health problem associated with dairy cow herds and is a major reason for excessive culling. Therefore, many studies have addressed this problem to further our understanding of the agents causing mastitis and their classification and virulence factors. This review summarizes the current knowledge regarding mastitis prevalence, the characteristics of its main causative agents, and the effects of mastitis on dairy production. The review also intends to provide guidance for future studies by examining external effects influencing dairy production in cows under field conditions.
Keywords: milk; dairy production; mastitis; causative agent; somatic cell count